Inland waterways & environmental protection (ECMT, 2006)
This report reviews experience in mitigating the environmental impacts of inland waterway development. It examines effective consultation and planning procedures across Europe. In particular it assesses the ways in which the EU Water Framework Directive affects the planning environment for international waterways and sets a new agenda for improving the ecological value of waterways. It makes recommendations on good practice and identifies the Danube river basin as the critical area for improvement: This is where the efforts of international governmental organizations and NGOs could most usefully be combined to develop a basin-wide environmental protection and waterway development strategy.--Publisher summary.